The effect of social media dependence on the perceived academic performance of university students in Cameroon: the role of psychological well-being and social anxiety - Jaff, Yvette Dufola; Ciftci, Dilan (Frontiers in Psychology, 2025)
Social media usage has increased, raising worries about its potential effects on individuals’ mental health. The present study aims to establish the relationship between social media dependence and academic performance and isolate how sense of belonging, and social anxiety mediate this effect. It offers an enhanced analysis of the phenomena by expanding on contributions provided by researchers from various areas in the literature. This research comprises a quantitative survey of 595 Cameroonian social media users to evaluate the suggested hypotheses. The results show that social media dependence generally has a beneficial indirect effect on perceived academic performance. The direct impact of social media dependence on perceived academic performance is negative but statistically insignificant. The findings shows that the significant positive influence of social media usage on the sense of belonging implies a positive impact of social media on Cameroonian students. However, the direct negative relationship between social media use and academic performance is not statistically significant and may be due to the fact that the benefits of social media use to the sample under investigation outweighs its negative effects. The findings have important policy implications. They suggest that higher education stakeholders in Cameroon should harness the potential of social media to enhance students’ sense of belonging and academic engagement. Policymakers could develop guidelines for integrating social media into learning environments in ways that support students’ psychological well-being and academic outcomes.